Students’ Responses to the Use of Songs in the EFL Classroom at a Public School in Bogotá: A Critical Approach (GIST – Education and Learning Research Journal, 2014)
This article reports the findings of an action research stydy aiming at fostering interest, participation, and self-expression in an EFL classroom at a public school in Usme, in the southeast of Bogotá. The study focuses on students’ responses to the use of songs with social content within a framework of literacy as a situated social practice and taking a critical view of pedagogy. A group of 11th graders participated in the study. Data was collected through questionnaires, field notes, interviews, and artifacts of students’ work. Results indicate that using songs as a socially-situated literacy practice in the EFL class can encourage students to participate in a more active and critical way. It can also trigger meaningful connections to real life issues allowing students to read the world and build bonds with their peers, using music as an opportunity to share ideas, thoughts, and feelings in a comfortable, respectful, and friendly environment.
Keywords: Responses to songs; songs with social content; EFL in a public school classroom; literacy as a situated social practice; critical pedagogy